Iodine-Mediated Neutral and Selective N-Boc Deprotection - G. Pavan Kumar; D. Rambabu; M. V. Basaveswara Rao; Manojit Pal (Journal of Chemistry)
A simple, efficient, and alternative method has been developed for the N-Boc deprotection of structurally diverse protected amines. Selective removal of N-Boc groups was achieved with excellent yields under a solvent-free condition or in a solvent using iodine as a catalyst. The methodology involving the first use of iodine for N-Boc deprotection of protected amines represents an effective and useful alternative to the previously reported methods.